Obesity detection rate among primary school students in the People's Republic of China: a meta-analysis - Jin Y; Ding L; Yao Y; Song X; Tang H; He L; Chen Y (Dove Medical Press, 2013)
Yue-long Jin,* Ling-ling Ding,* Ying-shui Yao, Xiu-li Song, Hui Tang, Lian-ping He, Yan ChenFaculty of Epidemiology and Statistics, School of Public Health, Wannan Medical College, Anhui, People's Republic of China*These authors contributed equally to this workBackground: Obesity has become a major public health problem worldwide. The prevalence of obesity is rising alarmingly among children and adolescents in the People's Republic of China, with an estimated 120 million now in the obese range. It is estimated that 8% of children in the People's Republic of China are obese and 12% are overweight.Methods: Eligible papers on the prevalence of obesity among primary school students in the People's Republic of China and published between 2006 and 2011 were retrieved from PubMed and from online Chinese periodicals, ie, the full-text databases of VIP, the Chinese National Knowledge Infrastructure, and Wan Fang. Meta-Analyst software was used to collate and analyze the detection rates cited in the papers retrieved.Results: After evaluation of the quality of the papers, 25 were finally included, giving a total sample population size for investigation of obesity of 219,763, in which 28,121 cases were detected. Meta-analysis showed that the combined obesity detection rate was 10.4% (95% confidence interval 8.6–12.6) among primary school students in the People's Republic of China, with a higher detection rate in boys (12.6%) than in girls (7.2%). The prevalence of obesity was higher in the north (11.8%) than in the south (9.5%), east (11.6%), and mid-west (8.0%) regions. Obesity defined according to the World Health Organization weight-for-height standard (14.3%) was higher than that using age-specific and gender-specific cutoff points for body mass index (9.0%).Conclusion: Our meta-analysis found an obesity prevalence rate of 10.4%, which does not seem as high as previous reports of childhood obesity rates in other countries. However, the prevalence of childhood obesity in the People's Republic of China is still worrisome, and is likely to rise even further if we fail to take effective and practical measures now.Keywords: primary school students, obesity, detection rate, meta-analysis